(untitled) (Veterinary Science, 2020)
The effects on the dynamic pattern of egg weight of five traits at sexual maturity were characterized in Campero Casilda hens. When the first egg was laid, body weight, age (an indicator of sexual precocity), weight of the first 10 eggs (an indicator of their initial weight), days needed to lay them (an indicator of regularity) and coefficient of variation of these weights (an indicator of uniformity) were recorded. All the eggs laid between sexual maturity and 72 weeks of age was weighed. Longitudinal data relating weekly average egg weight versus laying age were adjusted by non-linear regression with the Weatherup & Foster model. Birds were categorized by the values of each trait measured at sexual maturity and the category effect on the estimators of the function parameters was evaluated. Less precocious birds were heavier and laid larger eggs at the beginning of the cycle and in the asymptote, without differences on the egg weight maturation rate, in comparison to those more precocious. The latter began the laying period irregularly, requiring a greater number of days to lay the first 10 eggs and the weight of these had a higher coefficient of variation. The birds that began laying more uniform eggs in weight maintained that difference throughout the curve. Early selection of birds that begin laying at an older age, with greater body weight, more regularly and with heavier eggs uniform in size would show a favorable dynamic pattern in egg weight.